2017
DOI: 10.1371/journal.pone.0170655
|View full text |Cite
|
Sign up to set email alerts
|

SNP-Discovery by RAD-Sequencing in a Germplasm Collection of Wild and Cultivated Grapevines (V. vinifera L.)

Abstract: Whole-genome comparisons of Vitis vinifera subsp. sativa and V. vinifera subsp. sylvestris are expected to provide a better estimate of the valuable genetic diversity still present in grapevine, and help to reconstruct the evolutionary history of a major crop worldwide. To this aim, the increase of molecular marker density across the grapevine genome is fundamental. Here we describe the SNP discovery in a grapevine germplasm collection of 51 cultivars and 44 wild accessions through a novel protocol of restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 65 publications
6
55
2
Order By: Relevance
“…All these results are in agreement with previous studies attributing the low level of diversity among sylvestris and the absence of an inter-sylvestris population geneflow to the small size and the isolation of the sylvestris populations, and the high level of diversity within cultivated genotypes to the sexual crossing occurring during the grapevine domestication (This et al, 2006;Di Vecchi-Staraz et al, 2008;Vitti et al, 2013;Marrano et al, 2017;Riaz et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All these results are in agreement with previous studies attributing the low level of diversity among sylvestris and the absence of an inter-sylvestris population geneflow to the small size and the isolation of the sylvestris populations, and the high level of diversity within cultivated genotypes to the sexual crossing occurring during the grapevine domestication (This et al, 2006;Di Vecchi-Staraz et al, 2008;Vitti et al, 2013;Marrano et al, 2017;Riaz et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Also the SNPs heterozygosity was higher in the sativa grapevine compared to sylvestris, supporting previous observations based on SNPs analysis (Lijavetzky et al, 2007;Emanuelli et al, 2013;Marrano et al, 2017). With the exclusion of the accessions indicated as non-true-sylvestris, the SNPs heterozygosity of sylvestris further decreased to a range of 37-41% ( Supplementary Table S2).…”
Section: Discussionsupporting
confidence: 86%
“…In wild species the percentages were 73% and 27% respectively, while 71% and 29% were the values observed in hybrid/wild species genotypes. The current results slightly diverge from the usual transitions/transversions ratio found in grapevine (~1.5 in Salmaso et al , 2004; Lijavetzky et al , 2007; Vezzulli et al , 2008a; 2008b; ~2 in Marrano et al , 2017) as well as in beetroot (Schneider et al , 2001), potato (Simko, Haynes, & Jones, 2006) and cotton (Byers et al , 2012), while they are much higher than in soybean (Zhu et al , 2003) and almond (Wu et al , 2008).…”
Section: Resultscontrasting
confidence: 88%
“…SNP informativeness depends on their reliability among individuals and species and their high transferability rates probably are not consistent with a direct impact on the genetic sequence (when in coding regions). Considering previous studies in grapevine, a larger representativeness of MAF values <0.1 was found in non- vinifera genotypes and rootstocks, non-cultivated vinifera showed a MAF 0.05<x<0.3 while MAF >0.1 were severely represented by vinifera sativa (Lijavetzky et al , 2007; Vezzulli et al , 2008a; Emanuelli et al , 2013; Marrano et al , 2017). In the current study, the aim to focus on impacting mutations was achieved, since MAF ≤0.05 is a distinguishing mark for rare SNPs, which may be not considered interesting for SNP-arrays but which are most likely affecting the gene sequence and putatively protein activity.…”
Section: Resultsmentioning
confidence: 62%
“…Furthermore, collections of clones may represent a wider sampling of variation in the species than a population from a single geographic area. Our observations are not entirely uncommon-for instance, cultivated grapevine (Marrano et al, 2017) was more heterozygous than its wild counterpart and a study using microsatellites found that genetic diversity in hazelnut cultivars was similar or higher than wild populations in southern Europe (Boccacci et al, 2013).…”
Section: No Strong Domestication Bottleneck In Hazelnutmentioning
confidence: 48%